PC Programs for Adaptive Control of Drug Dosage Regimens and for Population Pharmacokinetic Modeling - Jelliffe, Roger W. (1990)
The USC*PACK PC clinical programs perform Bayesian adaptive control of drug dosage regimens. They improve prediction of serum levels of aminoglycosides and vancomycin, improve management of digoxin, reduce breakthrough arrhythmias in patients on lidocaine, and help optimize cancer chemotherapy. A new nonparametric EM (NPEM) program for population pharmacokinetic modeling computes the joint probability density function (PDF) for a 1-compartment pharmacokinetic model with IV dosing (see Figure 1). Output also includes marginal PDF plots, means, variances, modes, quartiles, skewness, kurtosis, and correlation coefficient. Results can be entered into population files for use with the PC clinical programs. The programs are available from the first author through a non-commercial license from the University of Southern California. (Supported by NIH Grant RR01629).